Perspective: The Public Health Case for Modernizing the Definition of Protein Quality. Issue 5 (8th May 2019) - Katz, David L; Doughty, Kimberly N; Geagan, Kate; Jenkins, David A; Gardner, Christopher D
ABSTRACT: Prevailing definitions of protein quality are predicated on considerations of biochemistry and metabolism rather than the net effects on human health or the environment of specific food sources of protein. In the vernacular, higher "quality" equates to desirability. This implication is compounded by sequential, societal trends in which first dietary fat and then dietary carbohydrate were vilified during recent decades, leaving dietary protein under an implied halo. The popular concept that protein is "good" and that the more the better, coupled with a protein quality definition that favors meat, fosters the impression that eating more meat, as well as eggs and dairy, is desirable and preferable. This message, however, is directly opposed to current Dietary Guidelines for Americans, which encourage consumption of more plant foods and less meat, and at odds with the literature on the environmental impacts of foods, from carbon emissions to water utilization, which decisively favor plant protein sources. Thus, the message conveyed by the current definitions of protein quality is at odds with imperatives of public and planetary health alike. We review the relevant literature in this context and make the case that the definition of protein quality is both misleading and antiquated. We propose a modernized definition that incorporates the quality of health and environmental outcomes associated with specific food sources of protein. We demonstrate how such an approach can be adapted into a metric and applied to the food supply.